Negotiating urbanities : an ethnography of Zimbabwean immigrants’ music informed-placemaking and musicking in Johannesburg - Vermeulen, Dorette (University of Pretoria, 2025)
Thesis (PhD (Music))--University of Pretoria, 2024.